PENGEMBANGAN INSTRUMEN TES KEMAMPUAN KOMUNIKASI MATEMATIS DALAM MATERI BANGUN RUANG DAN BANGUN DATAR DI SEKOLAH DASAR - Nurussama, Alfiana; Fitri, Kamiliya Nailah; Haeriska, Nadia; Zaidan, Rafi; Rahayu, Teten Ginanjar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aimed to develop a test instrument for mathematical communication skills among elementary school students, specifically on the topics of plane and solid geometry. The study used a Research and Development (R&D) method based on a modified 4-D model, which consisted of the define, design, and develop stages. The instrument was constructed based on three indicators: written text, drawing, and mathematical expression. Expert validation showed the instrument was highly valid, with a feasibility score of 80%. A limited trial was conducted with 16 sixth-grade students at MI Raudhatul Mubtadiin. The analysis using ANATES version 4.0.5 revealed that three out of five items had significant empirical validity. The instrument's reliability score was 0.59, which was categorized as moderate. Most items were of medium difficulty level, and their discriminating power ranged from good to sufficient. Based on these findings, the developed instrument was considered feasible for assessing students' mathematical communication skills in elementary school.